2003
DOI: 10.5897/ajb2003.000-1028
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus pumilus BpCRI 6, a promising candidate for cellulase production under conditions of catabolite repression

Abstract: Cellulose degrading organisms have been used for the conversion of cellulolytic materials into soluble sugars or solvents in several biotechnological and industrial applications. In this report, a mutant of Bacillus pumilus was obtained after chemical mutagenesis and screened for cellulase production. This mutant named BpCRI 6 was selected for its ability to produce cellulase under catabolite repression. Cellulase yield by BpCRI 6 was four times higher than that of the wild type under optimum growth conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The first catabolite repressed Bacillus pumilus with cellulase yield four times higher than the wild type strain was created through mutagenesis (Kotchoni et al 2003).…”
Section: Genetics and Recombinant Dna Technologymentioning
confidence: 99%
“…The first catabolite repressed Bacillus pumilus with cellulase yield four times higher than the wild type strain was created through mutagenesis (Kotchoni et al 2003).…”
Section: Genetics and Recombinant Dna Technologymentioning
confidence: 99%
“…This observation may also be applicable to mannanase production in mutants generated, because mannanase activity was reduced in some mutants in the presence of different sugar concentrations. Regulation of cellulase production had been well researched and documented (Moreno et al, 2001;Kotchoni et al, 2003); however, scanty information has been reported on regulation of mannanase production in microorganisms to date. The improvement in some of the mutants evaluated in media supplemented with mannose suggested that their regulatory genes might have lost their regulatory functions, thereby allowing the catabolite insensitive mutants to produce mannanase without inhibition by sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Lignocellulolytic microorganisms and their lignocellulolytic enzymes have many potential biotechnological applications ranging from the production of bio-fuel, chemicals, proteins, and to improving textiles, woodpulping and animal feeds for domesticated herbivores (Bhat and Bhat, 1997;Coughlan, 1985;Kotchoni et al, 2003;Ojumu et al, 2003). The white-rot, basidiomycete fungus, Phanerochaete chrysosporium, has attracted considerable research interest since it efficiently degrades all three components of lignocellulose (Baldrian, 2003;Tuomela et al, 2002;Yadav 2003).…”
Section: Introductionmentioning
confidence: 99%